SOCIETY AND SOCIAL MEDIA: PUBLIC OPINION ON THE PHENOMENON OF USTAD SOLMED AS A SYMBOL OF “RICH AND RELIGION” - Sari, Fitri Meliya; Nurdin, Hanifah; Situmeang, Marini Kristina; Putri, Sukma Ari Ragil; Syifaurrahmah, Syifaurrahmah (JURNAL AL-IJTIMAIYYAH, 2025)
This study analyzes the "Rich and Religious" image of Ustad Solmed as either a controversy or an inspiration through netizen comments on Instagram. This research reveals the dynamics of social media as a space for the production of imagery and social symbols that influence public perception. Using a qualitative approach and sentiment analysis, the study shows that netizens, as a normative majority, highlight the importance of balancing worldly affairs and the hereafter. Ustad Solmed's image is viewed negatively by netizens due to a worldly lifestyle deemed inconsistent with his status as a preacher. In the concept of social reception, acceptance or rejection of the balance between wealth and religiosity affects public perception of material and religious success. If society accepts this balance, a new symbol will emerge in religious practice, influencing religion-based economic life.